Increased Risk of Osteoporotic Fracture in Postgastrectomy Gastric Cancer Survivors Compared With Matched Controls: A Nationwide Cohort Study in Korea. (November 2019) - Shin, Dong Wook; Suh, Beomseok; Lim, Hyunsun; Suh, Yun-Suhk; Choi, Yoon Jin; Jeong, Su-Min; Yun, Jae Moon; Song, Sun Ok; Park, Youngmin
Abstract : OBJECTIVES: Gastrectomy can lead to bone loss. Previous studies have suggested that there is an increased risk of fracture in gastric cancer survivors. However, these studies were performed without proper control groups. Therefore, we used Korean national health insurance data to compare the fracture risk in gastric cancer survivors who received gastrectomy to that of the general population. METHODS: A total of 133, 179 gastric cancer survivors were included and matched to noncancer controls using 1:1 propensity score matching. Cox proportional hazards regression analysis was used to determine the relative risk of fracture between the gastric cancer survivors and matched controls. We also examined the factors associated with fracture in gastric cancer survivors. RESULTS: Compared with the matched controls, gastric cancer survivors had an elevated risk of osteoporotic fracture (hazard ratio [HR] 1.61, 95% confidence interval [CI] 1.53–1.70), which was most prominent in patients who underwent total gastrectomy (HR 2.18, 95% CI 1.96–2.44) and adjuvant chemotherapy (HR 2.01, 95% CI 1.81–2.23). In multivariate analysis, anemia was significantly associated with increased fracture risk (aHR 1.34, 95% CI 1.13–1.59), while decrease in weight >5% was not (aHR 1.06, 95% CI 0.89–1.25). DISCUSSION: Gastric cancer survivors who underwent gastrectomy had an increased osteoporotic fracture risk than did matched controls. Total gastrectomy, adjuvant chemotherapy, and anemia were associated with an even higher risk in these patients. Additional studies are needed to establish optimal strategies, such as screening for osteoporosis and preventive interventions, that will reduce fracture risk in this population.